Action learning and healthcare 2011–2022. (2nd September 2022) - Boak, George
ABSTRACT: This paper provides a review of the use of action learning in healthcare organisations, or by healthcare professionals, in the past decade, as evidenced in peer-reviewed journals. Action learning has a long history in healthcare and is perhaps particularly suited to an environment where wicked problems abound, where professional development is prized, and where many of the professions subscribe to reflective practice as a vehicle of development. A systematic search for literature in peer-reviewed English language journals was undertaken, followed by a process of pursuing references from the publications revealed by that search. Papers that provided accounts or evaluations of programmes and projects that included action learning were analysed. Common themes concerning purposes, processes, benefits and challenges were identified. Action learning was used for three purposes in the projects and programmes: to improve an aspect of healthcare services; to develop skills of the participants; to enhance collective capability. Whilst in some cases the intention was to achieve all three beneficial outcomes, it was apparent that in the majority of examples one or another of these purposes was prioritised as the principal aim of the programme or project.